NEED AND DUTIES OF ACCOUNTING IN BUSINESS ENTITIES - Nosirova Nargiza Tursunpolatovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article describes the need and tasks of modern accounting in economic entities and employment of the population.